Environmental impact and cost analysis of gas turbine cycles with steam injection and inter-stage turbine reheat. (18th August 2020) - Kayadelen, Hasan Kayhan; Ust, Yasin; Bashan, Veysi
Inter-stage turbine reheat is an effective gas turbine retrofit which can easily be used with simple and steam injected gas turbines as well. Owing to the uncertainties relating to an efficiency comparison of steam injected and no-injection cycle designs, thermoeconomics and environmental impacts have been considered to evaluate reheat and steam injection which regards pollutant emissions and environmental costs together. Being the complemental of the authors previous studies on steam injected gas turbines, simple, reheat, steam injected (STIG) and reheat steam injected (RHSTIG) gas turbine cycles are compared. Economic feasibility of steam injection as well as inter-stage turbine reheat are discussed according to 2018 plant cost data. Optimal cycle parameters are determined using a new comprehensive cycle model which permits to work with realistic working fluids, simulates the combustion process regarding 14 exhaust species and determines NOx and CO emissions.